Large-scale Mining and Dispossession in the South: a comparative analysis - William Sacher (Íconos)
In the present article, I evaluate the relevance of the concept of accumulation by dispossession in the case of large-scale mining in Africa and Latin America. I inventory and classify various types of dispossession processes associated with the implementation of large-scale mining activities in both regions. I evidence the relevance of this category in these two contexts, and its theoretical power, by showing how it captures essential elements of the dynamics of capitalism at the global level. In both regions, the processes constitutive of accumulation by dispossession are very similar. Social struggles against large-scale mining on both continents share common global determinants. This evidences the possibility of south-south alliances between these struggles.